IMPACTS OF FERTILIZER APPLICATION ON SOIL PROPERTIES AT KAHAROLE UPAZILA OF DINAJPUR DISTRICT IN BANGLADESH - Dhurbo Ronjon Roy; Md. Sirajul Islam; Bikash Chandra Sarker; Tanmoy Roy Tusher; Md. Humayun Kabir; Muliadi Muliadi; Shamim Al Mamun (AGRIVITA, Journal of Agricultural Science, 2016)
The study was conducted to investigate the impacts of fertilizer application on soil properties in Kaharole upazila of Dinajpur district in Bangladesh. Samples were collected to analyze the variation of soil nutrients in three cropping seasons: season-1 (March-April, 2013), season-2 (August-September, 2013) and season-3 (January-February, 2014). In each season 10 samples, 6 from conventionally cultivated soil (CCS) and 4 from organic fertilized soil (OFS), were collected from 10 randomly selected sampling points. The study observed acidic soil pH in all three cropping seasons, while soil pH was decreasing gradually with fertilizer application. The results of the study clearly depicted that all the soil nutrient contents and OM decreased with the application of fertilizers in different cropping seasons except Zn and Fe. The OFS contains relatively higher amount of OM and essential nutrients than CCS except Fe and Zn. The study shows that the continuous application of fertilizer in agricultural lands reduces soil fertility evolving nutrient deficiency in the soil; resulting in reduced crop productivity.